Paranormalism, Voting Intention, and Other Conspiracy Mentality Predictors in Sweden - Tidelius, Cristoffer (Temenos - Nordic Journal for the Study of Religion, 2024)
This article explores conspiracy mentality occurrence in Sweden as part of a 2020 survey of paranormal beliefs, practices, and experiences. Using the idea of a shared sociocultural milieu of alternative views and practices of knowledge as a departure point, the relationship between conspiracy mentality and paranormalism, viewed as instances of cultic, rejected, and stigmatized knowledge, is tested through multivariate regression. As part of the regression model, the effects of other social predictors (e.g. gender, income, and cultural values) are also assessed. A nonparametric analysis further explores the relationship between conspiracy mentality and voting intention. The results of multivariate regression show that the dependent variables only predict conspiracy mentality to a limited extent. Predictors that significantly contribute to predicting conspiracy mentality are gender (being male), higher levels of paranormalism, lower income, conservation as opposed to openness-to-change values, and self-transcendence as opposed to self-enhancement values. Meanwhile, the nonparametric test pointed to distinctly higher conspiracy mentality levels among sympathizers with the right-wing populist party the Sweden Democrats and those who favoured political parties not represented in parliament.